Pregnancy, parathyroids, and a crisis of calcium: unmasking hypercalcemic crises in pregnancy and beyond: a dual case report - Kumar, Ashish; Shaikh, Nissar; Padhy, Sanghamitra; Amara, Umm E.; Nashrah, Umme; Ummunnisa, Firdos (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Hypercalcemia is a rare complication during pregnancy, but when it occurs, it can lead to significant maternal and fetal morbidity. Primary hyperparathyroidism is the most frequent cause; however, other uncommon mechanisms such as parathyroid hormone-related protein (PTHrP) secretion by uterine fibroids have been described. We presented two cases. The first involved a 36-year-old primigravida at 34 weeks with severe hypercalcemia associated with a large uterine fibroid. Her condition required intensive care, urgent hemodialysis, and emergency cesarean section. Despite intraoperative complications, both mother and infant survived. The second case was a 37-year-old woman at 24 weeks who was found to have hypercalcemia with elevated parathyroid hormone (PTH) levels while hospitalized for pulmonary embolism. She was not a candidate for surgery and was successfully managed with hydration, calcitonin, vitamin D, and cinacalcet, achieving near-normal calcium levels before delivery. Both pregnancies resulted in live infants. Hypercalcemia in pregnancy requires a high index of suspicion and multidisciplinary management. These two cases highlight rare but important clinical scenarios: fibroid-associated humoral hypercalcemia and the use of cinacalcet for refractory primary hyperparathyroidism during pregnancy.